Examining the Relationship between Entrepreneurship Development Programs and Business Performance among Entrepreneurs in Tioman Island, Malaysia - HALIM, Muhammad Abi Sofian Abdul; OMAR, Khatijah; SAPUTRA, Jumadil; KAMARUDDIN, Siti Nor Adawiyah Azzahra; RAZALI, Md Khairul Azwan Md (Journal of Environmental Management and Tourism; Vol 12 No 3 (2021): JEMT Volume XII Issue 3(51) Summer 2021DO - 10.14505//jemt.v12.3(51).24, 2021)
Malaysia is an ecotourism destination that attracts foreign tourists, like ecotourism destinations in Bali, Chiang-Mai, Hat Yai, Phuket, and Aceh. Tioman Island is one of the most beautiful island destinations in Southeast Asia and receives an abundance of foreign tourists every year. This influx of tourists has built a new market segment and ecotourism concept approach, especially to micro and small entrepreneurs in Tioman Island. Some micro and small ecotourism operators in Tioman Island face competition problems with some medium-level companies that offer more competitive tourism products. This study examines the relationship between entrepreneurship development programs and business performance among entrepreneurs in Tioman Island. The findings showed that technology application and market access have a significant positive effect on business performance. Besides that, three other variables, namely, business networking, business financing, and training skill, do not significantly affect the business performance among entrepreneurs in Tioman Island. In conclusion, two significant variables that have contributed to entrepreneur business performance in Tioman Island are technology application and market access.  This study can provide opportunities for some micro and small entrepreneurs among the island community, such as lodging services, homestays, chalets, and recreational services.